2007
DOI: 10.1073/pnas.0705974104
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and dysregulated proinflammatory cytokine production in receptor activity-modifying protein 1-deficient mice

Abstract: Calcitonin gene-related peptide (CGRP) is thought to be a prominent neuropeptide in cardiovascular regulation and neuroimmune modulation. There are two isoforms of CGRP (␣CGRP and ␤CGRP), and the main CGRP receptors are probably composed of a calcitonin receptor-like receptor (CLR) and a receptor activity-modifying protein (RAMP)1. However, the physiological functions of CGRP that are mediated through the CLR/RAMP1 receptors remain to be clarified. For an improved understanding of the functions, we generated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 32 publications
4
134
1
Order By: Relevance
“…Lck-Cre transgenic mice were purchased from The Jackson Laboratory (Bar Harbor, ME). RAMP1-deficient mice were generated (32), and heterozygous knockout mice were backcrossed for 12 generations to C57BL/6 or BALB/c mice and used to generate the offspring used in the current study. All procedures, including experimental animals, were approved by the Experimental Animal Care and Use Committee of the Graduate School of Pharmaceutical Sciences, Osaka University.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lck-Cre transgenic mice were purchased from The Jackson Laboratory (Bar Harbor, ME). RAMP1-deficient mice were generated (32), and heterozygous knockout mice were backcrossed for 12 generations to C57BL/6 or BALB/c mice and used to generate the offspring used in the current study. All procedures, including experimental animals, were approved by the Experimental Animal Care and Use Committee of the Graduate School of Pharmaceutical Sciences, Osaka University.…”
Section: Methodsmentioning
confidence: 99%
“…1B). Incidentally, we estimate that the physiological concentration of CGRP is between 0.1 and 10 nM based on measurements of the CGRP concentration in serum (32). Therefore, the concentration (1 nM) of CGRP for promoting IL-9 seems to be adequate.…”
Section: Cgrp Upregulates Il-9 Production From Naive T Cells Via Its mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, aCGRP and bCGRP appear to equally suppress the production of tumour necrosis factor-a and interleukin-12 in bone marrow-derived dendritic cells stimulated with lipopolysaccharide. 7 Um et al reported that the expression of IL-1 in the brain was increased during the early and chronic stage of CI. 8 The aim of this study was to investigate the relationship between CI and human RAMP 1 gene using single-nucleotide polymorphisms (SNPs) and haplotypes in a Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“…RAMP1-deficient mice (RAMP1(À/À)) show inflammatory responses and CGRP signalling through CLR/ RAMP1 receptors, which have a crucial role in the regulation of proinflammatory cytokine production in dendritic cells. 7 Furthermore, Sundararajan et al 20 reported that the administration of troglitazone or pioglitazone 24 h before PPAR-g ligands markedly reduces infarction volume and improves neurological function following middle cerebral artery occlusion in rats. It is known that drugtreated animals show reduced inflammation, as evidenced by decreased immunoreactivity for microglial/macrophage markers and reduced interleukin-1b, cyclooxygenase-2 and inducible nitric oxide synthase.…”
mentioning
confidence: 99%